Does Patient Positioning and Portal Placement for Arthroscopic Subtalar Arthrodesis Matter?. Issue 3 (14th September 2018) - Shamrock, Alan; Glass, Natalie; Shamrock, Keith; Cychosz, Chris; Duchman, Kyle
Category: Arthroscopy Introduction/Purpose: Arthroscopic subtalar joint arthrodesis was first described over two decades ago. The procedure was originally performed with the patient in the lateral decubitus or supine position using anterolateral and posterolateral portals based on the fibula. More recently, several authors have advocated for prone positioning utilizing posteromedial and posterolateral portals. Proponents of the prone position cite improved intra-articular visualization with limited need for traction and more thorough preparation of the posterior facet. Multiple studies have compared arthroscopic to open subtalar arthrodesis and demonstrated similar fusion rates, lower morbidity, and a high level of patient satisfaction with the arthroscopic procedure. To our knowledge, this is the first study investigating how patient positioning and portal placement affects outcomes and morbidity for the arthroscopic procedure. Methods: A systematic review was performed according to PRISMA guidelines utilizing PubMed and Embase. All original studies with reported complication rates for arthroscopic subtalar arthrodesis were included. Two independent reviewers collected patient demographic data, operative positioning, complications, and outcomes including time to fusion and American Orthopaedic Foot and Ankle Society (AOFAS) scores. Patients were placed into the prone group if they were positioned prone with posterior portals or the lateral group if they underwent lateral portal placement. The rate of complications related to portal placement, nonunion rate, rate of painful hardware, and rate of revision were also recorded. The proportions of patients with specific complications in each group were determined and transformed using the Freeman-Tukey double-arcsine method to stabilize variances. Heterogeneity across studies was present as determined using the Q and I2 statistics or likelihood ratio test. Inverse-variance weighted random-effects models were used to evaluate the pooled estimates using R software. Results: A total of 484 feet in 468 patients with a mean follow-up of 36.1 months were included for analysis. Thirteen studies examined patients in the prone position (n=302) and seven articles looked at lateral portals (n=182). Mean AOFAS scores improved from 46.3 to 81.6 following surgery. Fusion was seen in 95.8% of feet at a mean of 10.9 weeks. The total complication rate was similar (p=0.620) between the prone (18.2%) and lateral (17.6%) groups. There was no difference observed in the rate of complications secondary to portal placement (p=0.919), rate of painful hardware (p=0.534), and revision rate (p=0.400) between the two groups. The prone group sustained 20 nonunions (6.6%) which was significantly more than the 2 nonunions (1.1%) found in the lateral group (p=0.039). Conclusion: Arthroscopic subtalar arthrodesis is an effective treatment option for subtalar joint pathology. We found a higher rate of nonunion when the patient is positioned prone and the arthroscopic portals are placed posteriorly. There was no difference in the rate of nerve/tendon injury, painful hardware, and revision surgery. AOFAS scores were improved regardless of portal placement. Limitations of our study include the variability in fusion hardware and use of bone graft for fusion augmentation between studies. We also were unable to account for surgeon experience, operative volume, and comfort level with the procedure. Further large scale prospective studies are warranted.